Lupus nephritis: management challenges during pregnancy - Gholizadeh Ghozloujeh, Zohreh; Singh, Tripti; Jhaveri, Kenar D.; Shah, Silvi; Lerma, Edgar; Abdipour, Amir; Norouzi, Sayna (Frontiers in Nephrology, 2024)
Lupus nephritis (LN), a severe complication of systemic lupus erythematosus (SLE), leads to significant kidney inflammation and damage and drastically increases mortality risk. Predominantly impacting women in their reproductive years, LN poses specific risks during pregnancy, including pre-eclampsia, growth restrictions, stillbirth, and preterm delivery, exacerbated by lupus activity, specific antibodies, and pre-existing conditions like hypertension. Effective management of LN during pregnancy is crucial and involves carefully balancing disease control with the safety of the fetus. This includes pre-conception counseling and a multidisciplinary approach among specialists to navigate the complexities LN patients face during pregnancy, such as distinguishing LN flare-ups from pregnancy-induced conditions. This review focuses on exploring the complex dynamics between pregnancy and LN, emphasizing the management difficulties and the heightened risks pregnant women with LN encounter.